Mapping of the atmospheric deposition of sulfur and nitrogen during the dry season 2016 in the Metropolitan zone of Merida, Yucatan, Mexico - Cerón Bretón, Rosa María; Cerón Bretón, Julia Griselda; Muriel García, M.; Lara Severino, Reyna del Carmen; Rangel Marrón, Marcela; Ramírez Lara, Evangelina; López Jiménez, D.; Rodríguez Guzmán, Abril; Uc Chi, Martha Patricia (2018)
Abstract. Atmospheric deposition of sulfur and nitrogen was measured in the Metropolitan Area of Merida, Yucatan in Mexico during the dry season of 2016. Passive samplers type "throughfall" based on ion exchange resins were used to measure the hydrological flows in a total of 9 sampling sites distributed throughout the city. The ions retained in the resin were analyzed by turbidimetry and colorimetry to determine Ammonium, Nitrate and Sulfate. Deposition fluxes of S and N obtained were 6.25 and 5.19 Kg ha-1 yr-1. Both, sulfur and nitrogen atmospheric deposition fluxes were higher in urban sites, exceeding almost 2 times, the reference values proposed internationally for sensitive ecosystems. From the analysis of wind roses and air masses trajectories, it was possible to establish that during this climatic season, in addition to the local vehicular emissions, regional emissions generated upwind (from E-SE) contributed to atmospheric deposition of these ions. Finally, N and S deposition fluxes and their relationship with criteria pollutants were assessed, and maps for atmospheric deposition fluxes of Ammonium, Sulfate and Nitrate were generated using geo-statistical tools in order to identify critical deposition zones in this Metropolitan zone.